2019
DOI: 10.1002/jsfa.9694
|View full text |Cite
|
Sign up to set email alerts
|

Fucus vesiculosus extracts as natural antioxidants for improvement of physicochemical properties and shelf life of pork patties formulated with oleogels

Abstract: BACKGROUND There is limited information in the literature concerning the feasibility of using algal extracts as natural additives for improvement of the quality and shelf‐life of meat products. Hence, a Fucus vesiculosus extract (FVE) at the concentrations of 250 mg kg‐1 (FVE‐250), 500 mg kg‐1 (FVE‐500) and 1000 mg kg‐1 (FVE‐1000) were added to pork patties with linseed oil oleogel as a fat replacer. RESULTS Total polyphenol content of FVE was determined to be 20 g phloroglucinol equivalents 100 g‐1 extract. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 31 publications
5
40
1
1
Order By: Relevance
“…This is the case of the brown seaweeds Ascophyllum nodosum, Bifurcaria bifurcate, and Fucus vesiculosus used in liver pâté with sufficient capacity to avoid the use of synthetic antioxidants, questioned for their harmful effects on health, thus providing lipid and protein stability to the product [168]. These results were confirmed in pork patties [169]. The high contents of phlorotannin in Fucus vesiculosus could explain its positive effects on oxidation stability (lipid and protein oxidation) and sensory attributes.…”
Section: Ros Antioxmentioning
confidence: 77%
“…This is the case of the brown seaweeds Ascophyllum nodosum, Bifurcaria bifurcate, and Fucus vesiculosus used in liver pâté with sufficient capacity to avoid the use of synthetic antioxidants, questioned for their harmful effects on health, thus providing lipid and protein stability to the product [168]. These results were confirmed in pork patties [169]. The high contents of phlorotannin in Fucus vesiculosus could explain its positive effects on oxidation stability (lipid and protein oxidation) and sensory attributes.…”
Section: Ros Antioxmentioning
confidence: 77%
“…Indeed, the textural features of meat products change with respect to original product as reported by Barbut et al, who showed a firmer and more rubbery comminute beef product when beef fat was replaced directly with canola oil. To solve these issues, the structuring of vegetable oils using the incorporation of edible structured gels has received much attention in recent years …”
Section: Introductionmentioning
confidence: 99%
“…The use of emulsion gels shows strong potential for application in the food industry in general and in the meat industry in particular, especially for the development of healthier meat products . In the scientific literature there are several work where emulsion gels prepared with vegetable oils are used as fat replacers in the development of low‐fat meat products . These emulsions are prepared mainly with (i) chia oil, avocado oil, canola, olive oil or linseed oil, because these oils showed a high polyunsaturated fatty acid content in their fatty acid profile, and (ii) several flours such as oat, whey, or banana.…”
Section: Introductionmentioning
confidence: 99%